PENGARUH ATTACHMENT ORANGTUA DAN TEMAN TERHADAP PENYESUAIAN DIRI MAHASISWA BARU - Zulfa Indira Wahyuni (Jurnal Harkat : Media Komunikasi Gender, 2022)
Abstract. The first year of college is a critical period experienced by new students to make adjustments academically, socially, and emotionally that will have an impact on academic success. The purpose of this research is to find out what factors that influence the adjustment of new students. The variables measured were the influence of parent attachment and peer attachment. This study used a quantitative approach involving 200 students in second semester. The sampling technique used was convenience sampling technique. The measuring instrument used is the Student Adaptation to College Questionnaire (SACQ) developed by Baker and Syrk (1989) and the Inventory of Parent and Peer Attachment – Revised (IPPA-R) measuring instrument developed by Gullone and Robinson (2005). The data analysis technique used is multiple regression. Based on the results of hypothesis testing the conclusion is that there is a significant effect of parent attachment and peer attachment on new students’ adaptation. Furthermore, the variables with significant coefficient values are father attachment, mother attachment, and friend attachment, with the largest contribution from the variable father attachment. Further research is recommended to look at other factors outside of this study that also affect the adjustment of new students. Abstrak. Tahun pertama kuliah merupakan periode kritis yang dialami mahasiswa baru untuk melakukan penyesuaian secara akademik, sosial, dan emosional yang akan berdampak pada keberhasilan akademik selanjutnya. Tujuan dilakukannya penelitian ini adalah untuk melihat faktor-faktor yang mempengaruhi penyesuaian diri mahasiswa baru. Variabel yang dilihat adalah pengaruh atatchment orangtua dan attachment teman. Penelitian menggunakan pendekatan kuantitatif dengan melibatkan 200 mahasiswa semester 2. Pengambilan sampel dilakukan dengan teknik convenience sampling. Alat ukur yang digunakan adalah Student Adaptation to College Questionnaire (SACQ) yang dikembangkan oleh Baker dan Syrk (1989) dan alat ukur Inventory of Parent and Peer Attachment – Revised (IPPA-R) yang dikembangkan oleh Gullone dan Robinson (2005). Teknik analisis data yang digunakan adalah regresi berganda. Berdasarkan hasil uji hipotesis, kesimpulannya adalah ada pengaruh yang signifikan attachment orangtua dan attachment teman terhadap penyesuaian diri mahasiswa baru. Selanjutnya, variabel yang nilai koefisiennya signifikan adalah attachment ayah, attachment ibu, dan attachment teman, dengan sumbangan terbesar dari variabel attachment ayah.